Hemagglutination inhibiting antibodies and protection against seasonal and pandemic influenza infection. Issue 2 (February 2015) - Fox, Annette; Mai, Le Quynh; Thanh, Le Thi; Wolbers, Marcel; Le Khanh Hang, Nguyen; Thai, Pham Quang; Thu Yen, Nguyen Thi; Minh Hoa, Le Nguyen; Bryant, Juliet E.; Duong, Tran Nhu; Thoang, Dang Dinh; Barr, Ian G.; et al.
Summary Objectives Hemagglutination inhibiting (HI) antibodies correlate with influenza vaccine protection but their association with protection induced by natural infection has received less attention and was studied here. Methods 940 people from 270 unvaccinated households participated in active ILI surveillance spanning 3 influenza seasons. At least 494 provided paired blood samples spanning each season. Influenza infection was confirmed by RT-PCR on nose/throat swabs or serum HI assay conversion. Results Pre-season homologous HI titer was associated with a significantly reduced risk of infection for H3N2 (OR 0.61, 95%CI 0.44–0.84) and B (0.65, 95%CI 0.54–0.80) strains, but not H1N1 strains, whether re-circulated (OR 0.90, 95%CI 0.71–1.15), new seasonal (OR 0.86, 95%CI 0.54–1.36) or pandemic H1N1-2009 (OR 0.77, 95%CI 0.40–1.49). The risk of seasonal and pandemic H1N1 decreased with increasing age (both p < 0.0001), and the risk of pandemic H1N1 decreased with prior seasonal H1N1 (OR 0.23, 95%CI 0.08–0.62) without inducing measurable A/California/04/2009-like titers. Conclusions While H1N1 immunity was apparent with increasing age and prior infection, the effect of pre-season HI titer was at best small, and weak for H1N1 compared to H3N2 and B. Antibodies targeting non-HI epitopes may have been more important mediators of infection-neutralizing immunity for H1N1 compared to other subtypes in this setting.